Two‐scale fusion method of infrared and visible images via parallel saliency features. Issue 16 (24th February 2021) - Duan, Chaowei; Xing, Changda; Lu, Shanshan; Wang, Zhisheng
Abstract : An efficient fusion method of infrared and visible images is proposed based on the parallel saliency features. The method integrates significant feature information from the source images of multiple imaging modalities into a single fused image in a multi‐scale domain, while suppressing visual artefacts and retaining more detail and texture information. First, the input images are decomposed into two‐scale image representations, namely the base and detail layers, using a Gaussian filter. Second, the parallel saliency features of the high contrast and detail textures are captured to acquire the saliency maps. The contrast saliency weight map of the base layers based on the weighted local intensity energy aims to highlight the salient targets in infrared images and preserve the high‐intensity regions in visible images, while the detail saliency weight map of the detail layers using the structure tensor to extract the detail texture information. Finally, the final image is reconstructed by the fused base and detail layers. Sufficient experimental results convincingly demonstrate that the presented method can achieve a comparable or superior performance compared with several state‐of‐the‐art fusion methods via subjective assessments and objective evaluations, and it is more suitable for the practical applications due to the high computing efficiency.